1999
DOI: 10.1016/s0092-8674(00)80761-8
|View full text |Cite
|
Sign up to set email alerts
|

Short Dysfunctional Telomeres Impair Tumorigenesis in the INK4aΔ2/3 Cancer-Prone Mouse

Abstract: Maintenance of telomere length is predicted to be essential for bypass of senescence and crisis checkpoints in cancer cells. The impact of telomere dysfunction on tumorigenesis was assessed in successive generations of mice doubly null for the telomerase RNA (mTR) and the INK4a tumor suppressor genes. Significant reductions in tumor formation in vivo and oncogenic potential in vitro were observed in late generations of telomerase deficiency, coincident with severe telomere shortening and associated dysfunction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
237
0
5

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 354 publications
(253 citation statements)
references
References 55 publications
11
237
0
5
Order By: Relevance
“…Studies using knockout mice have demonstrated that depending on the cell type and genomic context, telomeres may exert dual and even opposite effects in cancer, on one side limiting tumor growth, while on the other side promoting tumorigenesis. 30,31 It has been hypothesized that longer telomeres and especially telomerase activation, leading to longer cellular survival and, therefore, the accumulation of genetic mutations might be the cause of an increased cancer risk incidence with longer TL. 32,33 Moreover, based on animal and in vitro studies, it seems that an early activation of telomerase via exogenous regulators of human telomerase reverse transcriptase, along with an increased lymphocyte growth and a subsequent selection of cells with increased transforming potential may characterize several virus-related lymphoid malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using knockout mice have demonstrated that depending on the cell type and genomic context, telomeres may exert dual and even opposite effects in cancer, on one side limiting tumor growth, while on the other side promoting tumorigenesis. 30,31 It has been hypothesized that longer telomeres and especially telomerase activation, leading to longer cellular survival and, therefore, the accumulation of genetic mutations might be the cause of an increased cancer risk incidence with longer TL. 32,33 Moreover, based on animal and in vitro studies, it seems that an early activation of telomerase via exogenous regulators of human telomerase reverse transcriptase, along with an increased lymphocyte growth and a subsequent selection of cells with increased transforming potential may characterize several virus-related lymphoid malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Both in vitro and in vivo, overexpression of telomerase in cancer cells appears to be crucial for tumor progression (Greenberg et al, 1999;Hahn et al, 1999a, b;Gonzalez-Suarez et al, 2000Elenbaas et al, 2001;Artandi et al, 2002). On the other hand, studies on mice lacking the telomerase RNA gene demonstrate that critical telomere shortening and telomere instability can favor initial stages of cancer formation and cooperates with p53 deficiency to favor carcinogenesis Rudolph et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…This model has led some to propose that telomerase inhibition may be an effective anti-neoplastic strategy (Counter et al 1992). In support of this model, mice lacking both mTERC and p16 INK4A show a reduced incidence of tumor formation compared with mice lacking p16 INK4A alone (Greenberg et al 1999). This experiment suggests that in certain genetic backgrounds, telomere dysfunction can impair tumorigenesis.…”
Section: Barriers To Immortalization: Crisismentioning
confidence: 95%